Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Kantor Lurah YZ Kabupaten Bengkalis - kurniawan, teuku reza; Herman, Herman (Eko dan Bisnis: Riau Economic and Business Review, 2024)
The research will be carried out at the Lurah YZ Department of Rupat district of Bengkalis. The aim of this research is to find out the impact of the quality of service on public satisfaction in the Lurah YZ Prefecture of Rupat district of Bengkalis. The sample in this study consisted of 96 people who had been simplified using the Slovene formula. In this study the sample method uses the accidental sampling technique. Data analysis in this study uses descriptive and quantitative methods. Based on the results of the analysis of the study, it was found that the Quality of Service had a significant influence on public satisfaction at the Office of Lurah YZ Rupat district of Bengkalis thitung = 7,255 > ttable = 2,000. The result of simple linear regression obtained the equation of regression Y = 16,674 + 0,476X, this means the result of the research is the same as the research hypothesis. The R2 value of 0.359 means that the significant impact of Service Quality on public satisfaction in Lurah YZ Prefecture of Rupat district of Bengkalis is 35.9%, while 64.8% is influenced by other variables not studied in this study